2017
DOI: 10.1021/acs.cgd.7b00761
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Total Spontaneous Resolution

Abstract: We achieved chiral symmetry breaking through continuous crystallization, which enables the continuous industrial production of chirally pure crystals. For this, a novel recycling platform that mimics a continuous cooling crystallization process with a hot concentrated feed and an outflow of cold suspension was developed and tested. A virtually enantiopure steady-state was realized by seeding a clear supersaturated achiral solution with enantiopure seed crystals at the start of the experiment. Seeding with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 31 publications
(66 reference statements)
0
30
0
Order By: Relevance
“…It has recently been shown that PlasDIC can be applied to help monitor crystal growth, with potential applications in the pharmaceutical industry [26,28]. The results presented above lead us to suggest that ICOA-GOR might be applied to provide chiral sensitivity in this context, an important addition given the importance of chirality to the pharmaceutical industry [42]. We envisage using ICOA-GOR to determine the sign of the optical rotation of a crystal in conjunction with a computer algorithm trained with knowledge of the crystal's habit to determine the crystal's orientation; together, this information will reveal the chirality of the crystal.…”
Section: Appearance Using Icoa-gormentioning
confidence: 96%
“…It has recently been shown that PlasDIC can be applied to help monitor crystal growth, with potential applications in the pharmaceutical industry [26,28]. The results presented above lead us to suggest that ICOA-GOR might be applied to provide chiral sensitivity in this context, an important addition given the importance of chirality to the pharmaceutical industry [42]. We envisage using ICOA-GOR to determine the sign of the optical rotation of a crystal in conjunction with a computer algorithm trained with knowledge of the crystal's habit to determine the crystal's orientation; together, this information will reveal the chirality of the crystal.…”
Section: Appearance Using Icoa-gormentioning
confidence: 96%
“…As a result, secondary nucleation is an excellent approach to make new crystals in continuous crystallization experiments as seed crystals would continuously convert a supersaturated feed solution into secondary nuclei. 16 A proof of concept of the continuous generation of secondary nuclei has been reported for glycine and paracetamol, where secondary nuclei were formed through continuous contact nucleation. 17 Alternatively, continuous shear-induced secondary nucleation through fluid shear should also be feasible.…”
Section: Introductionmentioning
confidence: 96%
“…After the formation and dispersion of secondary nuclei, the crystal surface becomes available to induce secondary nucleation again, provided that the solution remains sufficiently supersaturated. As a result, secondary nucleation is an excellent approach to make new crystals in continuous crystallization experiments as seed crystals would continuously convert a supersaturated feed solution into secondary nuclei . A proof of concept of the continuous generation of secondary nuclei has been reported for glycine and paracetamol, where secondary nuclei were formed through continuous contact nucleation .…”
Section: Introductionmentioning
confidence: 99%
“…Chiral resolution, occurring during the spontaneous resolution or chiral symmetry breaking, continues to be a subject of great interest in the pharmaceutical industry and material sciences . In our previous report, we observed chiral resolution of β‐ dl –phenylalanine by [Ni( RR ‐L)] 2+ and [Ni( SS ‐L)] 2+ (Scheme ) enantiomers selectively binding β‐ d ‐phenylalanine and β‐ l ‐phenylalanine to form [Ni( RR ‐L)(β‐ d ‐HPhe)](ClO 4 ) 2 and [Ni( SS ‐L)(β‐ l ‐HPhe)](ClO 4 ) 2 (L = 5,5,7,12,12,14‐hexamethyl‐1,4,8,11‐tetraazacyclotetradecane, Phe = phenylalanine), respectively.…”
Section: Introductionmentioning
confidence: 96%